Nanocomposites of few-layer graphene oxide and alumina by density functional theory calculations. Issue 3 (February 2016) - Polfus, Jonathan M.; Løvvik, Ole Martin; Rørvik, Per Martin; Bredesen, Rune
Abstract: The atomistic and electronic structure and oxygen stoichiometry of nanocomposites between alumina and graphene oxide were investigated by density functional theory calculations. The nanocomposite was described as interfaces between α-Al2 O3 (0001) surfaces and graphene oxide; the latter was defined with oxygen bound as epoxy groups and a C:O atomic ratio of 4:1. The optimized composite structure with 1–3 layers of graphene oxide in between Al2 O3 contains bridging AlOC bonds at the interface. Reduction of the composite was investigated by removal of oxygen from the interface AlOC bonds, within the graphene oxide layers and in Al2 O3 . It was found that removal of oxygen within the graphene oxide layers is essentially independent of the Al2 O3 interface, i.e., the same as in pure graphene oxide. Oxygen was, however, more strongly bound in the interface AlOC bonds by 0.80 eV, and reduction of graphene oxide to graphene is accordingly preferred within the graphene oxide layers rather than at the oxide interface.